Seasonal vertical distribution, abundance, biomass, and biometrical relationships of ostracods in Golfo Dulce, Pacific coast of Costa Rica - Morales-Ramírez, Alvaro (2008)
The abundance, biomass, and vertical distribution of ostracods, as well as some biometrical relationships, were investigated during a 24h cycle over a period of two days, both in May and September 1995 in Golfo Dulce, on the Pacific coast of Costa Rica. The sampling was performed according to the tidal cycle, in addition to vertical sampling at depths of 0-10-20-30-40-50-70-80 and 100m to determine temperature, salinity, oxygen concentration, and Secchi depth. Zooplankton samples were taken using a close-up Nansen net in three sampling layers: 0-20m, 20-50m and 50-100m. Ostracod abundance (adults and developmental stages) and total dry weight biomass were estimated from one aliquot obtained with a Folsom Plankton Splitter. Ostracod dry weight biomass was measured by taking between five and fifty organisms of a single development stage. Four ostracod species were found: Cypridina americana, Euchonchoecia chierchiae, Porroecia spinirostris, and Porroecia sp.. Biometrical relationships for the former two species revealed significant differences between all stages both in average length and season (p<5.10-7), and seasonal differences in the size between males and females for both species, with strong sexual dimorphisms in the males. Seasonal differences in biomass were found in C. americana due to the fact that ovigerous females weighed twice as much in May than in September. Species dominance in ostracod abundance alternated between E. chierchiae and C. americana, depending on the season. In general terms, both species were primarily found at depths within the first 20m in May, while at depths greater than 50m abundance was only 2% and 0.4% for C. americana and E. chierchiae, respectively. In May, some differences in the day/night rhythms were detected in C. americana in all developmental stages, except the first stages, which were always found at depths within the first 20m, in contrast to E. chierchiae, where all development stages, except stage I, remained in the first sampled layer, regardless of circadian periodicity. Differences in vertical patterns may be related to a predator avoidance behavior or to utilization of food resources related to ontogenetic components, at least for C. americana. Ostracod abundance in Golfo Dulce, in comparison with the oceanic environment, is extraordinary high in spite of the oceanic features of this gulf. Both species play an important role in the trophic ecology of Golfo Dulce, where C. americana is a detritivorous species and a facultative predator, whereas E. chierchiae grazes on organic matter. This is the first ecological study on ostracods from Costa Rican coastal waters. Rev. Biol. Trop. 56 (Suppl. 4): 125-147. Epub 2009 June 30.